Evidence of an inhibitory restraint of seizure activity in humans - Schevon, Catherine A.; Weiss, Shennan A.; McKhann, Guy; Goodman, Robert R.; Yuste, Rafael; Emerson, Ronald G.; Trevelyan, Andrew J. (Nature communications, 2012)
The location and trajectory of seizure activity is of great importance, yet our ability to map such activity remains primitive. Recently, the development of multi-electrode arrays for use in humans has provided new levels of temporal and spatial resolution for recording seizures. Here, we show that there is a sharp delineation between areas showing intense, hypersynchronous firing indicative of recruitment to the seizure, and adjacent territories where there is only low-level, unstructured firing. Thus, there is a core territory of recruited neurons and a surrounding 'ictal penumbra'. The defining feature of the 'ictal penumbra' is the contrast between the large amplitude EEG signals and the low-level firing there. Our human recordings bear striking similarities with animal studies of an inhibitory restraint, indicating that they can be readily understood in terms of this mechanism. These findings have important implications for how we localize seizure activity and map its spread. Seizure activity in the brain is characterized by the recruitment of cortical neuronal activity. Schevon and colleagues study seizure activity in human subjects and find that the recruitment of neurons is hypersynchronous and that there is an intrinsic restraint on the propagation of this activity.